2022
DOI: 10.1177/17479541221111462
|View full text |Cite
|
Sign up to set email alerts
|

Balancing sport and academic development: Perceptions of football players and coaches in two types of Norwegian school-based dual career development environments

Abstract: Sports-friendly and elite sport schools seek to support pupils by providing balanced support which is intended to facilitate success both in sport and in academic work. This study investigates how ambitious football players in Norway experience the advantages and challenges of undertaking a ‘dual career’ as student-athletes. Eight players and five coaches (two club coaches and three school coaches) in total were interviewed from two sports-friendly schools and two elite sports schools, and the data were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…We did not find a notable difference in student athletes’ perceived RC with the roles according to school type (i.e., private elite sports school or public sports-friendly school). In contrast, a recent study of football players and their coaches found that the close integration of the school and club settings in elite sports schools enables better communication dynamics regarding the overall workload compared to less structured sports-friendly schools [ 10 ]. There are several possible explanations for these contradictory findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We did not find a notable difference in student athletes’ perceived RC with the roles according to school type (i.e., private elite sports school or public sports-friendly school). In contrast, a recent study of football players and their coaches found that the close integration of the school and club settings in elite sports schools enables better communication dynamics regarding the overall workload compared to less structured sports-friendly schools [ 10 ]. There are several possible explanations for these contradictory findings.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, the Norwegian national curriculum introduced elite sports as an optional subject in public schools [ 6 , 7 , 8 , 9 ]. Today, more than 110 private and public schools offer the elite sports program [ 10 ], one of Norway’s most popular programs among high school students [ 8 ]. Although differences exist between the programs offered by private and public schools [ 5 , 10 ], a fundamental similarity is that student athletes in the “Elite Sport” program will likely experience a considerable increase in physiological (i.e., training load) and psychological (i.e., stress associated with academic demands, social commitments, employment, and sports participation) loads after enrolment [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the intention of a dual career sport program is to help talented athletes achieve the highest possible level in sports as well as in education, the two aims can be difficult to combine. Several studies ( van Rens et al, 2015 ; Küttel et al, 2020 ; Sæther et al, 2022 ) have found that most student athletes who stated that they wanted to reach the international top level prioritized their sport over their studies when studying at a sport school with a dual career sport program profile, contradicting the intention of such a program. A specific example is found in a study by Ronkainen et al (2018) who showed that ice hockey coaches affected student athletes to prioritized their athletic career over their studies.…”
Section: Introductionmentioning
confidence: 99%